THE HOLOCENE-TO-RECENT GEOMORPHOLOGICAL, SEDIMENTOLOGICAL AND STRATIGRAPHIC DEVELOPMENT OF THE LOWER PERAK RIVER AND ITS COASTAL-DELTAIC PLAIN - ABD. MANAF, MAIZATUL ASNIDA (2015)
This study focuses on the geomorphology, sedimentology and stratigraphy of lower Perak coastal deltaic-plain in relation to Holocene sea level change. The Perak River is located on the west flank of Peninsular Malaysia and can be divided into four geographic regions; lower and upper parts for both of the upstream and coastal areas. The channel pattern occurred in this area includes the straight-braided and meandering. The river flow changes it direction from north to south before drifted easterly to the west at Teluk Intan.